Interpersonal problems, optimism and copying styles among Women with conversion disorder: A correlational study. - Hafiza Amna Munir; Naeema Sarfraz (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the relationship between interpersonal problems, optimism and copying styles among women with conversion disorder. Methods: Co-relational study was conducted from August to October 2017 at different hospitals of Lahore city in Pakistan. Translated interpersonal problem (IPP-32), brief cope, life orientation revised questionnaires were administered on sample population to assess relationship of optimism, interpersonal problems, pessimism and copying styles. Statistical package for social sciences was used for data analysis. Results: 50 women with conversion problem approached, 98% responded. Among them, 12(26.7%) most of the participants belonged to very lower socio economic class as well as most of the participants 17(37.8%) belonged to lower socio economic class. Overall mean age of the subjects was 24.44+55 years. Subjects were classified on qualification basis most of them were uneducated. Conversion problem was more common among adolescence age group females (M=88.78, SD=18.21). Inverse relationship found between interpersonal problems and optimism variables. Self-blaming copying style was significantly correlated among conversion women. Other copying ways such as use of emotional support, social inhibition, pessimistic tendency and interpersonal problem of behavioral disengagement were also having positive relationship with each other among conversion women. However, no highly significant relationship was found among all variables. Conclusion: A considerable proportion of study indicated that social inhibition, emotional support most commonly self-blaming kind of non-adaptive ways pessimism, optimism and interpersonal problem of behavioral disengagement all were associated with each other among women with conversion disorder.